Time-intensity models for intermittent sports games using the European Handball Championship 2020 as an example: Mixed models and more - Schäfer, R.; Venzke, J.; Niederer, D.; Manchado, C.; Platen, P. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Training load terminology can be confusing. Parameters like the "normalized distance" are commonly used to describe the load profile in sports games. The interpretation of such parameters is not always straightforward and depends on the question asked and the data processing. Causal effect estimates are often the target, but this is even harder for observational studies (e.g., analysis of tournament data) compared to experiments. In handball, research interest was placed on positional differences and decreasing intensity over time. Our aim is to highlight methodological pitfalls when interpreting observational data from intermittent sports games and show techniques to overcome t